Path Planning Method for Hydraulic Heavy-duty Manipulators Considering Dynamic Overturning Stability - Song Zepeng; Liu Fang; Huang Taotao (Jixie chuandong)
Aiming at the dynamic overturning stability of hydraulic heavy-duty manipulators, a path planning method based on the improved rapidly-exploring random tree（RRT） algorithm is proposed. Different from the static stability checking only in dangerous conditions, the algorithm takes the optimal dynamic overturning stability of the manipulator as the goal, and carries out the optimal path planning in the joint space of the manipulator. Taking a seven-dimensional array of seven joint variables as sampling points, combined with positive kinematics and moment method, the dynamic overturning stability calculation model of the manipulator is established, in order to enhance the heuristic of the algorithm. The random points of the optimal anti-overturning moment under the corresponding pose are selected as the sampling points. The simulation experiments on the Matlab platform show that the overturning margin of the improved RRT algorithm is increased by 37%, 28% and 38% respectively under three typical conditions, and the anti-overturning stability of the hydraulic heavy-duty manipulator platform is effectively improved.